Infrastructure for Delivery of Integrated Child Development Services and Uptake of Pre-school Education Services: Insights from Palghar, India. (January 2021) - Joe, William; Kumar, Abhishek; Rajpal, Sunil; Misra, Archa; Alambusha, Ruby; Sharma, Smriti; Subramanian, S. V.
The Integrated Child Development Services (ICDS) is a flagship programme of the Government of India and is delivered through a vast network of Anganwadi Centres (AWCs)—Courtyard Shelters—across rural and urban areas of the country. The ICDS is, however, affected by low coverage of various ICDS services, in general, and preschool education (PSE) services, in particular. This article aims to understand whether status of AWC infrastructure can have an effect on enhancing the coverage of PSE component. The article has twofold objectives: (a) to develop an AWC infrastructure index (AII), which can be applied to support programmatic monitoring and evaluation by ICDS and (b) to comprehend the association of AII with attendance and uptake of PSE services. Based on descriptive and econometric analysis of the AWC infrastructure data from Palghar (Maharashtra, India), it is demonstrated that better infrastructure is associated with higher PSE service coverage. The article concludes by highlighting the relevance of investing in AWC infrastructure, refurbishments and quality improvements to expand ICDS service coverage, particularly for the PSE services.